Essays in honor of Peter C.B. Phillips - Phillips, P. C. B.; Park, Joon Y.; Chang, Yoosoon; Fomby, Thomas B. (Emerald, 2014)
These essays honor Professor Peter C.B. Phillips of Yale University and his many contributions to the field of econometrics. Professor Phillips's research spans many topics in econometrics including: -non-stationary time series and panel models -partial identification and weak instruments -Bayesian model evaluation and prediction -financial econometrics and -finite-sample statistical methods and results. The papers in this volume reflect additions to and amplifications of many of Professor Phillips' research contributions. Some of the topics discussed in the volume include panel macro-econometric modeling, efficient estimation and inference in difference-in-difference models, limiting and empirical distributions of IV estimates when some of the instruments are endogenous, the use of stochastic dominance techniques to examine conditional wage distributions of incumbents and newly hired employees, long-horizon predictive tests in financial markets, new developments in information matrix testing, testing for co-integration in Markov switching error correction models, and deviation information criteria for comparing vector autoregressive models.
Keywords: Econometrics.; Economic forecasting -- Statistical methods.; Panel analysis -- Econometric models.; Time-series analysis.; elektronické knihy; electronic books